Protecting Forested Areas in Non-Forest Zone through The Ecological Fiscal Transfer Scheme in Indonesia: A case study from Kutai Timur district - Mohamad Nasir (Forest and Society, 2022)
Ecological fiscal transfer (EFT) is an incentive scheme of budgetary transfers from different levels of a government (central and regional) to reward performances in environmental management. In Indonesia, EFT is mainly intended to protect forest zones or protected areas but does not include forested areas in the non-forest zone. This article investigates the opportunities and challenges of adopting the EFT scheme as a policy instrument to maintain the forested areas in Kutai Timur, a district in East Kalimantan province with the largest forested areas in its non-forest zone. This study applies a socio-legal approach along with a regulatory simplification instrument to examine the laws and regulations surrounding the adoption of an EFT scheme in Kutai Timur district.  It demonstrates that the Kutai Timur district government can adopt the EFT scheme, given that they have the authority to manage the APL and village funds allocation. The scheme has no specific requirements or standards, identifying priority issues in the environmental sector. To adopt the scheme, the district government should develop criteria and indicators by considering the goals and priorities of district development, the data availability, and the opportunity for every village to implement it. The preparation of these criteria and indicators must be carried out in a participatory and accountable process to be well accepted by the stakeholders. Further, the district government requires integrating the EFT scheme in district policies on village funds allocation. By implementing the EFT scheme, the district government can encourage village governments and villagers to protect and manage forested areas in their village.